The association of post‐operative delirium with patient‐reported outcomes and mortality after lung transplantation. Issue 5 (16th March 2021) - DeBolt, Claire L.; Gao, Ying; Sutter, Nicole; Soong, Allison; Leard, Lorriana; Jeffrey, Golden; Kleinhenz, Mary Ellen; Calabrese, Daniel; Greenland, John; Venado, Aida; Hays, Steven R.; Shah, Rupal; et al.
Abstract: Post‐operative delirium after lung transplantation is common. Its associations with health‐related quality of life (HRQL), depression, and mortality remains unknown. In 236 lung transplant recipients, HRQL and depressive symptoms were assessed as part of a structured survey battery before and after transplantation. Surveys included the Geriatric Depressive Scale (GDS) and Short Form 12 (SF12). Delirium was assessed throughout the post‐operative intensive care unit (ICU) stay with Confusion Assessment Method for ICU. Delirium and mortality data were extracted from electronic medical records. We examined associations between delirium and changes in depressive symptoms and HRQL using linear mixed effects models and association between delirium and mortality with Cox‐proportional hazard models. Post‐operative delirium occurred in 34 participants (14%). Delirium was associated with attenuated improvements in SF12‐PCS (difference ₋4.0; 95%CI: −7.4, −0.7) but not SF12‐MCS (difference 2.2; 95%CI: −0.7, 5.7) or GDS (difference ₋0.4; 95%CI: −1.5, 0.7). Thirty‐two participants died during the study period. Delirium was associated with increased adjusted hazard risk of mortality (HR 17.9, 95%CI: 4.4, 72.5). Delirium after lung transplantation identifies a group at increased risk for poorer HRQL and death within the first post‐operative year. Further studies should investigate potential causal links between delirium, and poorer HRQL and mortality risk after lung transplantation.